2019
DOI: 10.1002/jpen.1738
|View full text |Cite
|
Sign up to set email alerts
|

Tutorial: Nutrition Therapy in Eosinophilic Esophagitis—Outcomes and Deficiencies

Abstract: Eosinophilic esophagitis (EoE) is a chronic, immune-mediated disease that presents with symptoms of esophageal dysfunction, which vary by age. Diagnosis is made by upper endoscopy with esophageal biopsies to identify dense eosinophilic inflammation with at least 15 eosinophils per high-power field. Untreated, EoE can progress from inflammatory to esophageal remodeling with fibrosis and stricture formation. Food antigens are the primary trigger of inflammation in EoE. The most common food antigen triggers are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Adequate dietary education and review from a dietitian supplemented by comprehensive patient resources are essential to successful implementation of elimination diets in EoE. 31,32 Barriers to compliance with elimination diets include financial resources, inadequate social support systems, patient motivation, and access to appropriate substitute foods. 11,26 Our findings have shown that majority of foods required for the 2-, 4-, and 6FED can be sourced from a major supermarket; however, patients may require support from a dietitian to identify these foods and incorporate them into their diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate dietary education and review from a dietitian supplemented by comprehensive patient resources are essential to successful implementation of elimination diets in EoE. 31,32 Barriers to compliance with elimination diets include financial resources, inadequate social support systems, patient motivation, and access to appropriate substitute foods. 11,26 Our findings have shown that majority of foods required for the 2-, 4-, and 6FED can be sourced from a major supermarket; however, patients may require support from a dietitian to identify these foods and incorporate them into their diet.…”
Section: Discussionmentioning
confidence: 99%
“…Without the modelling adjustments made by experienced accredited practising dietitians, the 4‐ and 6‐FED meal plans were nutritionally inadequate in iodine, riboflavin, and calcium. Adequate dietary education and review from a dietitian supplemented by comprehensive patient resources are essential to successful implementation of elimination diets in EoE 31,32 . Barriers to compliance with elimination diets include financial resources, inadequate social support systems, patient motivation, and access to appropriate substitute foods 11,26 .…”
Section: Discussionmentioning
confidence: 99%
“…If failure to thrive or nutritional deficiencies are suspected, biochemical tests (i.e., bone and iron metabolism, serum albumin, and prealbumin) should be performed. When a micro- or macronutrient deficiency is confirmed, nutritional supplements should be promptly provided ( Table 4 ) ( 66 ).…”
Section: Nutritional Considerations and Patient Educationmentioning
confidence: 99%
“…The basic form is the six-food elimination diet (SFED), based on elimination of milk protein, eggs, wheat, soy, peanuts and sea food. Compared to other empiric elimination diets, such as the four-food elimination diet (exclusion of milk protein, eggs, wheat and soy) or the two-food elimination diet (exclusion of milk protein and eggs), the SFED has been proven to be highly effective in inducing remission [ 14 , 15 , 16 ]. After achieving remission, eliminated allergens should be reintroduced into the diet one by one (step-down approach), and a control biopsy should be performed after each reintroduction to detect the potential food trigger.…”
Section: General Treatment Recommendations For Eoementioning
confidence: 99%